BIOSORCIÓN OF Cr (VI) BY LEMON RIND, CITRUS LIMONIUM, TREATED - Armijo C., Javier (2009)
We tested biosorcion of chromium (VI) using lemon rind, citrus limonium, treated. The original lemon rind passes first through a stage of desmetoxilación with sodium hydroxide solution, 0.2M, pH 10, and in a second stage is subject to a process of crosslinking with solution diclorurm calcium, 0.2M, pH 2. The tests showed that chromium (VI) can be removed from its aqueous solutions, up to 75% of its initial concentration in twenty minutes.